Sanitary conditions and associated factors of school canteens in the Federal District, Brazil - Erika Blamires Porto; Bethsáida Abreu Schmitz; Elisabetta Recine; Maria de Lourdes Rodrigues (Fundação Oswaldo Cruz (FIOCRUZ), 2015)
The aim of this study was to survey the health conditions of school canteens in the Federal District, Brazil and identify possible matches between their sanitation profile and other characteristics. This included type of school, canteen manager's educational level, and management system. We observed a few nutritionists, employees, and qualified technical personnel in charge in most of the 182 canteens that we visited. In 80% of the canteens, the sanitation and hygiene conditions were considered "inadequate" and only 8% were considered "good" or "very good." Of all the inspection items, potable water supply had the highest compliance rate (98.4%); however, safe food handling practices had the lowest compliance rate (2.7%). Among the other observed items, canteens in private schools, management system, canteen manager's educational level, employee training, and the presence of a nutritionist were positively associated (p < 0.05) with the best hygiene conditions. Overall, we observed that the sanitation/hygiene inspection performance of canteens in the Federal District, particularly in public schools, is critical to the health of students. It is our hope that the government and school communities implement cooperative actions to raise the sanitation/hygiene levels at school canteens.